2004
DOI: 10.1539/sangyoeisei.46.117
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Educational Effects of Group Counseling with Visual Aids: Efforts to Prevent Diabetes in a Business Office Setting

Abstract: We made this report with a view to clarifying the effects of group counseling with visual aids for railway workers enjoying improved health conducted as a part of prevention activities for lifestyle-related diseases such as diabetes. We employed the use of visual aids including slides, samples of blood and the measurement of vascular age on diabetes, and carried out group counseling to improve the interest, knowledge and realization of diabetes and lifestyle. This group counseling was carried out both with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…According to the self-reported questionnaire on the availability of the program from some participants, problems in accessing the menu and input of the record were reported (data not shown). However, Sato et al reported a follow up rate of primary preventive activities for lifestylerelated disease at a worksite after 2 months of just 18.0% 28) . Takahashi et al reported that a systematic review of lifestyle intervention for health promotion of older adults showed a low drop-out rate when the intervention program targeted people who had health risks or who had diseases at clinics, hospitals, and worksites 29) .…”
Section: Discussionmentioning
confidence: 99%
“…According to the self-reported questionnaire on the availability of the program from some participants, problems in accessing the menu and input of the record were reported (data not shown). However, Sato et al reported a follow up rate of primary preventive activities for lifestylerelated disease at a worksite after 2 months of just 18.0% 28) . Takahashi et al reported that a systematic review of lifestyle intervention for health promotion of older adults showed a low drop-out rate when the intervention program targeted people who had health risks or who had diseases at clinics, hospitals, and worksites 29) .…”
Section: Discussionmentioning
confidence: 99%